Effects of spray-drying temperatures on powder properties and antioxidant activities of encapsulated anthocyanins from black glutinous rice bran - Nattapong Kanha (2018)
The objective of this study was to determine the effects of spray drying temperature on the powder properties and antioxidant activities of encapsulated black glutinous rice (BGR) bran anthocyanins. The anthocyanins in BGR bran was extracted using acidified ethanol. The extract was encapsulated with maltodextrin (DE10) using spray drying at various inlet air temperatures (IAT; 140, 160 and 180°C). The results revealed that increasing IAT enhanced productivity with lower energy consumption, encapsulation efficiency, solubility, dispersibility, wettability, flowability and surface smoothness of the microcapsules. In contrast, total anthocyanin content (TAC), bulk density and color values (a*, C* and h°, respectively) of the microcapsules were decreased by increasing the IAT. Reducing power and DPPH radical scavenging activity of anthocyanin powders were not significantly different. In addition, anthocyanin powder produced using 180oC IAT showed the greatest encapsulation efficiency (96.72 ± 0.61%), solubility (87.42 ± 1.26%), dispersibility (86.45 ± 0.93%) and repose angle (23.50 ± 0.61 degree).